ESTRATEGIA EDUCATIVA EN EL RECONOCIMIENTO DE SIGNOS DE ALARMA RESPIRATORIOS POR PARTE DE MADRES COMUNITARIAS DEL PROGRAMA FAMILIA, MUJER E INFANCIA DEL INSTITUTO COLOMBIANO DE BIENESTAR FAMILIAR, COLOMBIA. - NARANJO ROJAS, ANISBED; ARANGO ARANGO, ANA CRISTINA; ARZUSA JARAMILLO, MARÍA JOSÉ; ALEJANDRA GIRALDO, MARÍA (Archivos de Medicina (1657-320X))
Objective: to identify the level of knowledge before and after an educational strategy in the recognition of respiratory alarm signs by community mothers of the Family, Women and Children program of the Colombian Family Welfare Institute, between June and July. 2017. Materials and Method: quantitative, quasi-experimental, with pretest and posttest. Extracurricular educational strategy, of a participatory type, aimed at community mothers of the FAMI program in the recognition of respiratory alarm signs. A sample of 33 community mothers belonging to the North headquarters. A database was created, analyzed in the SPSS version 20 format, subject to review, validation and data consistency. The measurement instruments were validated in a pilot test that had the same characteristics of the study population. Results: it was found that there is a significant difference after applying the educational strategy, the level of knowledge was measured through a questionnaire that evaluates the level of knowledge in respiratory alarm signs, finding an average difference of 2.03 between the pretest and the posttest, a confidence interval of 95% (0.81- 3.92) and a value of P 0.004. Conclusions: health education programs become the perfect strategy to minimize complications associated with ignorance of good care practices in the individual, especially when care is developed in the early childhood population.